Perbandingan Pengelolaan Risiko Kredit Perbankan Syariah dan Perbankan Konvensional - Muhammad Iqbal (University of Merdeka Malang, 2017)
This study aims to identify factors that can be used as indicators in reducing the incidence of credit risk in sharia banking and conventional banking. The variables that become observations include banking performance in each group and macroeconomic performance. The banking performance variables include credit risk itself as measured by problem financing, growth in financing, growth in third-party funds, and banking size. While macroeconomic variables include national income, interest rates, and inflation. Autoregressive and distributed lag methods are used to identify which variables can be used as indicators. The results showed that all identified factors can be an indicator in the process of credit risk control both in sharia banking and conventional banking. Only credit growth in conventional banking alone cannot be used as an indicator of credit risk control.DOI: https://doi.org/10.26905/jkdp.v21i3.1318